Smaller beaks for colder winters: Thermoregulation drives beak size evolution in Australasian songbirds - Friedman, Nicholas R; Harmáčková, Lenka; Economo, Evan P; Remeš, Vladimír (Evolution, 2017)
Birds' beaks play a key role in foraging, and most research on their size and shape has focused on this function. Recent findings suggest that beaks may also be important for thermoregulation, and this may drive morphological evolution as predicted by Allen's rule. However, the role of thermoregulation in the evolution of beak size across species remains largely unexplored. In particular, it remains unclear whether the need for retaining heat in the winter or dissipating heat in the summer plays the greater role in selection for beak size. Comparative studies are needed to evaluate the relative importance of these functions in beak size evolution. We addressed this question in a clade of birds exhibiting wide variation in their climatic niche: the Australasian honeyeaters and allies (Meliphagoidea). Across 158 species, we compared species' climatic conditions extracted from their ranges to beak size measurements in a combined spatial-phylogenetic framework. We found that winter minimum temperature was positively correlated with beak size, while summer maximum temperature was not. This suggests that while diet and foraging behavior may drive evolutionary changes in beak shape, changes in beak size can also be explained by the beak's role in thermoregulation, and winter heat retention in particular.
Keywords: Body Temperature Regulation; Animals; zpěvní ptáci; Phylogeny; zobák; termoregulace; zvířata; biologická evoluce; Beak; nízká teplota; fylogeneze; Biological Evolution; Songbirds; Cold Temperature